The impact of ESG scores on financial performance: Evidence from property and real estate firms listed on the Indonesia Stock Exchange (2020–2024) - Raisya Gita Amalia; Rahmadani Nur Permanawati (Universitas Nusa Cendana, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative approach was employed using panel data regression analysis to assess the influence of the ESG Overall Score, Environmental Score (ESGE), Social Score (ESGS), and Governance Score (ESGG) on Return on Assets (ROA), with firm size and leverage included as control variables. The results indicate that the ESG Overall Score has a positive and significant effect on ROA, suggesting that firms with stronger ESG performance achieve higher profitability. Furthermore, the environmental, social, and governance dimensions each exhibit positive and significant relationships with financial performance, with the social dimension exerting the strongest influence. These findings support stakeholder theory, demonstrating that effective ESG practices enhance operational sustainability, strengthen stakeholder trust, and improve long-term competitiveness. This study extends the ESG literature by providing empirical evidence from Indonesia’s property and real estate sector and highlights the strategic importance of comprehensive ESG implementation in improving corporate financial performance. Keywords: ESG Score; ROA;Financial Performance; Property and Real Estate Sector ;Indonesia